DETECTION OF AEDES AEGYPTI RESISTANCE TOWARDS CYPERMETHRIN USING POLYMERASE CHAIN REACTION (PCR) TECHNIQUES IN AMBARAWA SEMARANG REGENCY - Cahyati, Widya Hary; Fitriani, Laila (Unnes Journal of Public Health, 2020)
Ambarawa Regency is one of the endemic sub-districts since 2017 which always accounts for the highest DHF cases in Semarang Regency. Molecular detection of Aedes aegypti resistance towards sipermetrin using Polymerase Chain Reaction (PCR) techniques. The study was conducted to see mutations in the Aedes aegypti VGSC gene. This research was a pure experimental study. The Aedes aegypti samples examined were 10 in every village taken from 3 endemic DHF villages with high fogging intensity in Ambarawa. The research used random sampling techniques taken with ovitrap which was first installed during the month of August. Resistance detection test using the PCR method were conducted at the Banjarnegara Research and Development Center in September. Data were analyzed descriptively to illustrate the results of the study. The results showed that in Tambakboyo Village, 2 samples were susceptible (V / V), 7 samples were detected as homozygous (G / G) resistant, 1 sample was detected as heterozygous (V / G) resistant; in Kupang District 5 samples were detected as being homozygous resistant (G / G) and 5 samples were detected as heterozygous resistant (V / G); and in Panjang Village 1 susceptible sample (V / V), 8 samples were detected as homozygous resistant (G / G), 1 sample was detected as heterozygous resistant (V / G). Based on the results of mutation studies had been found in the VGSC gene in codon V1016G. The proper implementation of management, selection and rotation of insecticides is expected to reduce the risk of resistance in the Aedes aegypti mosquito population.